Transforming Democratic Leadership: the possible resolution of collective action problems. : A topic for discussion (Ágora de Heterodoxias, 2023)
This text is a synthesis of the project: "Democratic Leadership for a transforming change towards Human Development", which has been developed by a team of the Theory and Method of Planning Area of the Center for Development Studies (Cendes) of the Central University of Venezuela (UCV). The Project consists of the identification of the theoretical and methodological relationships around Planning-Development, and the construction of an integrated Framework of Reference for the formation of a democratic and transforming leadership.
Keywords: Leadership; change; development; collective action